Expectancy Theory As A Determination Of Net Promoter Score (Nps): Increasing The NPS Value Of Services - Yosie William Iroth; Judith Sinaga (UNIVED Press, 2024)
The wave of digital transformation had been boosted and accelerated by the pandemic, but whether or not this opportunity is leveraged by the industry especially the financial service industry remains a big question. The question around which aspect of digital transformation would best impact the industry is another challenge. In the discussion of reputation management, the customer aspect is a critical factor, thus the question of whether or not the customer perceived the benefit or accepted the digital transformation also need to be discover. Let’s go back to the financial service industry which is the focus on this research, are the services provided by financial service company had fulfilled their expectation and thus would result in a higher Net Promoter score for the company. This research uncover that providing digital services is not enough when it comes to NPS it requires understanding of the customer hopes and acting upon it.